Financial Technology In Financial Inclusion - Harnavela Sofyan; Khariidatul Bahiyyah; Santy Sriharyati (EKOBIMA, 2023)
Financial technology is a technological innovation in financial products and services. Financial technology can become a new solution to increase the growth of financial inclusion. The term financial inclusion became a trend after the 2008 financial crisis. Financial inclusion is the availability of access to various financial institutions, products, and services to the needs and capabilities of the community to improve people's welfare. For this reason, this research examines the role of financial technology in increasing financial inclusion, by explaining how financial technology has an impact on financial inclusion in improving people's welfare. Financial inclusion is a national development strategy aimed at promoting economic growth through equal distribution of income, poverty alleviation, and financial system stability. Financial inclusion in its role requires an increase in financial technology considering that along with technological developments, the banking sector alone is not enough to achieve the goal of financial inclusion. Financial technology plays an important role in expanding access to financial services for the public, this is reflected in the financing provided by several financial technology companies. With this financing, it is hoped that the level of social welfare will also increase along with the influence of fintech in Indonesia's financial inclusion.